The impact of the 1996 US Immigration Policy Reform (IIRIRA) on Mexican migrants' remittances - Matias Vaira-Lucero; Daehoon Nahm; Massimiliano Tani (Institute for the Study of Labor (IZA), 2012)
This paper investigates the effect of the US Illegal Immigrant Reform and Immigrant Responsibility Act of 1996 (IIRIRA) on the remitting patterns of Mexican immigrants. Using data from the Mexican Migration Project (MMP128), we find that a significant effect on remittance flows from illegal migrants took place after the implementation of the IIRIRA. This is consistent with the hypothesis that illegal immigrants are risk-averse agents who transfer more money to their home country as a mechanism to insure themselves against higher degrees of uncertainty within their host countries. Furthermore, this finding confirms previous research that conditions and policies in the host country affect migrants' remitting behaviour, and migrants' motivations are not only altruistic but also self-interested. Given that migrants' remittances and their savings are important sources of capital formation in many sending countries and of savings in the countries that host them, a better understanding of the effect that migration policies have on remittance flows can lead to more informed policies that can transcend the home security aspects that often dominate discussions about illegal migration.
urn:nbn:de:101:1-201301188827
Keywords: F22; F24; J61; 330; remittances; legal status; uncertainty; policy reform; illegal migrants; Mexico; migration policy; Rücküberweisung (Migranten); Mexikaner; Illegale Einwanderung; Einwanderungsrecht; Reform; USA; Mexiko